PARIWISATA SEKSUAL ANAK : UPAYA PERLINDUNGAN ANAK BERKAITAN DENGAN SEX CHILD TOURISM - Faisal, Izzah Amila (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Tourism is the one of the main revenue in Indonesia.  A large of number tourists comes to Indonesia every day with the different country, culture and aim. Base on our international visitor that come from different country, they bring together with their culture when visit Indonesia. Therefore   tourism has the positive and negative impact for our culture. As Indo people we have to keep save our basic identity from the acculturation. But in other hand tourism have some negative effect. Child Sex tourism is the issue of this paper and become one of the phenomena that occur in Indonesian tourism. Even though Indonesia have the national and international regulation that protect child from sex exploitation, but in the real life still find the same issue regarding child sex tourism. The purpose of this research is to find and identify the factor that be the main cause of child sex tourism to be able to conclude the efforts of legal protection rights of children and also against sex child tourism practice and protect the from any kind of sexual crime practice. As we know that the children are our future generation that must be protected all of their rights. Law enforcement officers together with the government need more improvement efforts to against sexual crime practice specialy that happen with the children in Indonesia.
Keywords: Child sex tourism; sex exploitation